A brief Analysis of Huang Qin Decoction in Treatise on Cold Damage and Modern Pharmacological Studies - Guan, Xiangran; Tian, Shihan; Wang, Chunqiu (Journal of Contemporary Medical Practice, 2025)
Huangqin Decoction is one of the ancient prescriptions in traditional Chinese medicine. It was first recorded in Zhang Zhongjing’s Treatise on Cold Damage and Miscellaneous Diseases at the end of the Eastern Han Dynasty. The formula consists of four herbs: Scutellaria baicalensis, white peony root, licorice, and jujube. This simple prescription is potent, with the ability to clear heat, dry dampness, relieve pain, and stop diarrhea. Numerous studies have reported that Huangqin Decoction has anti-inflammatory, antipyretic, analgesic, and antibacterial effects. In modern clinical practice, it is primarily used for treating gastrointestinal diseases associated with damp-heat stagnation. This article aims to summarize and discuss the modern pharmacological research on the complete formula of Huangqin Decoction and its herbal composition, providing a reference for further studies on the specific mechanisms of action of Huangqin Decoction.